Geometry : the easy way - Leff, Lawrence S. (Hauppauge, NY : Barron's Educational Series, 1997)
Explains the principles of plane geometry and includes practice exercises and model problems.
Rev. ed. of: Barron's geometry the easy way. 2nd ed. c1990.
Includes index.
Keywords: Geometry, Plane